The prevalence of polycystic ovaries in infertility by laparoscopy ‎ - Tahereh Ziaie; Seyedeh Marzieh Rahebi; Fatemeh Rafat; Shahin Savadzadeh (Journal of Holistic Nursing and Midwifery)
Introduction: The problem that engaged obstetrics & gynecologists was causes of polycystic ‎ovaries (PCO) and one of its important clinical complications is infertility. Laparoscopy has high ‎value and precision in disease diagnosis.